Sugarcane Bagasse Torrefaction for fluidized bed gasification - Pedroso, Daniel Travieso; Machin, Einara Blanco; Cabrera-Barjas, Gustavo; Flores, Mauricio; Urra, Héctor Grandón; De Carvalho, Felipe Solferini; Silva Dos Santos, Maria Isabel [UNESP]; Machín, Adrian Blanco [UNESP]; Canettieri, Eliana Vieira [UNESP]; Pérez, Néstor Proenza; Lacava, Pedro Teixeira; Dos Santos, Leila Ribeiro; et al. (MDPI, 2021)
Sugarcane bagasse has a great potential to be used as biofuel; however, its use as feedstock in fluidized bed reactors is hampered due to its fibrous nature, low apparent density, high moisture content, and difficulties with its fluidization. The present study evaluated the torrefaction of sugarcane bagasse to propose suitable process conditions that balance the properties of the fuel obtained in the torrefaction and the process’s energy requirements. Based on the thermogravimetric analysis and previous reports, two final process temperatures (230 °C and 280 °C) and residence times (35 and 45 min) for the same heating rate (5 °C/min) and nitrogen flow (1 L/min) were evaluated. Within the experimental conditions evaluated, it can be concluded that for 30 min of residence time, the average target temperature of 230 °C should be high enough to produce a stable torrefacted bagasse with a 3.41% reduction in the volatile content and obtain 98.85% of energy yield. Higher temperatures increase the feedstock’s carbon content and energy density, but the reduction in energy yield and the fraction of volatiles do not justify higher temperatures or longer residence times for pretreating the sugarcane bagasse.
Keywords: Biomass; Entrained flow gasifier; Gasification; Sugarcane bagasse; Torrefaction